Classification Of PM10 And Fall Out Dust Sampling In The Iron Ore Mining Industry, Northern Cape Province Of South Africa - Rautenbach, Johannes, Jacobus. (Central University of Technology, Free State, 2019)
Introduction: Fall-out dust is present in the iron ore mining industry and are generated by open cast mining activities and regulated by legislation. The aim of this study was to determine the concentrations of different dust types deposited at various dust monitoring points. Methods: Single dust bucket (SDB), and multi directional dust bucket (MDB) methods were used to collect the dust samples. The collected dust was further evaluated for particulate matter smaller than 10 μm (PM10) and analysed for the chemical composition of iron ore fall-out dust with possible impacts on humans and the environment. The influence of environmental parameters on the dust concentrations was also determined. Monitoring was conducted over a twelve-month period. The SDB method was sampled at eight different monitoring points and the MDB method at four monitoring points. Fall-out dust concentrations were determined for all dust sample collections. The sample concentration values were compared to the limit values of the South African National Standard 1929, ambient air quality limits for common pollutants. PM10 monitoring was done at three monitoring points. The chemical analyses of sampled dust for 42 elements was done at an accredited laboratory. The data on environmental parameters used in this study were collected from a centrally located weather station. Results: The mean dust concentrations for SDB and MDB never exceeded the limit of 600 mg/m²/day for residential areas. The highest level for mean SBD was recorded in November when the wind speed was relatively high. The highest level of mean MDB and mean SDB + MDB fall-out dust where recorded in September. The mean values for SDB, MDB and SDB + MDB were higher from August towards the end of the year as the mean wind speed and relative humidity increased from August. The mean PM10 concentrations never exceeded the limit and the highest level was recorded in February, when the mean wind speed was the lowest with the mean relative humidity the highest of the study period. The highest mean total fall-out dust concentrations of were recorded in September when the predominant wind direction was south south west (SSW). August had the second highest mean total fall-out dust concentration when the wind was predominant in the opposite direction of North. More than 50% of months the wind blows from a predominant multi direction and bi-directional of north west north (NWN) and north east (NE). The mean total PM10 concentration of all the PM10 monitoring points was calculated per month. The fluctuation in the mean total PM10 concentrations per month was limited when the wind directions were multi-directional and bi-directional respectively. Elements with concentrations below the detectable level (BDL) of less than 0.0001 mg/kg had been excluded and only 25 elements are reported on. The results showed that there are only three elements namely calcium, iron and copper that had noticeable higher concentrations than the other elements. Discussion and conclusion: One of the prominent findings of this study was that the individual buckets of the multi-directional dust bucket did not produce significant differences, making the use of this type of bucket redundant. From the results it could be thus concluded that using single dust bucket systems could be used to monitor in a mining environment. Interestingly, the PM10 concentrations never exceeded the limit in the year of study. Furthermore, concentrations of the chemical elements were within environmental and occupation exposure limits. However, copper and iron demonstrated noticeably high concentrations, with copper and iron concentrations exceeding both the environmental and occupational exposure limits at all sampling points. From this study, it can be concluded that wind direction does not has a major influence on the type of method used for measuring fall out dust. Although the limit was never exceeded, the results indicated that the use of the multi-directional bucket system seems to be redundant. Wind speed has an influence on the rate of PM10 dust particle depending on the monitoring point location in relation to dust producing operations. Applicable legislation is needed to monitor the elemental chemical content of dust when conducting environmental sampling.